Low-power laser in the treatment of exuberant manifestations of congenital syphilis (Research, Society and Development, 2021)
Congenital syphilis is still a reality in third world countries, resulting in local and systemic complications that compromise the patient's quality of life. Thus, the aim of this article is to present a clinical case of a 34-day-old male lactating patient diagnosed with congenital syphilis. On clinical examination, the patient presented numerous ulcerations and tissue lesions in the mouth, face and limbs. As adjuvant therapy, the standard approaches were associated with the application of low-power laser. After 8 sessions of photodynamic therapy, there was complete remission of the clinical condition presented, returning quality to the patient's tender life. With the case presented, the manifestations and complications of syphilis are still challenging. It is essential that the multidisciplinary team is able to diagnose and treat congenital syphilis as early as possible; the dentist must have knowledge of the various clinical manifestations of it to help in the correct diagnosis and treatment before the onset of symptoms. Low power laser photobiomodulation therapy appeared to satisfactorily accelerate the tissue repair process. The patient's response to the instituted treatment was gratifying.